Genomic characterization and radiation tolerance of Naganishia kalamii sp. nov. and Cystobasidium onofrii sp. nov. from Mars 2020 mission assembly facilities - Patrick Leo; Marcus de Melo Texeira; Atul M. Chander; Nitin K. Singh; Anna C. Simpson; Andrey Yurkov; Fathi Karouia; Jason E. Stajich; Christopher E. Mason; Kasthuri Venkateswaran (IMA Fungus)
Abstract During the construction and assembly of the Mars 2020 mission components at two different NASA cleanrooms, several fungal strains were isolated. Based on their colony morphology, two strains that showed yeast-like appearance were further characterized for their phylogenetic position. The species-level classification of these two novel strains, using traditional colony and cell morphology methods combined with the phylogenetic reconstructions using multi-locus sequence analysis (MLSA) based on several gene loci (ITS, LSU, SSU, RPB1, RPB2, CYTB and TEF1), and whole genome sequencing (WGS) was carried out. This polyphasic taxonomic approach supported the conclusion that the two basidiomycetous yeasts belong to hitherto undescribed species. The strain FJI-L2-BK-P3T, isolated from the Jet Propulsion Laboratory Spacecraft Assembly Facility, was placed in the Naganishia albida clade (Filobasidiales, Tremellomycetes), but is genetically and physiologically different from other members of the clade. Another yeast strain FKI-L6-BK-PAB1T, isolated from the Kennedy Space Center Payload Hazardous and Servicing Facility, was placed in the genus Cystobasidium (Cystobasidiales, Cystobasidiomycetes) and is distantly related to C. benthicum. Here we propose two novel species with the type strains, Naganishia kalamii sp. nov. (FJI-L2-BK-P3T = NRRL 64466 = DSM 115730) and Cystobasidium onofrii sp. nov. (FKI-L6-BK-PAB1T = NRRL 64426 = DSM 114625). The phylogenetic analyses revealed that single gene phylogenies (ITS or LSU) were not conclusive, and MLSA and WGS-based phylogenies were more advantageous for species discrimination in the two genera. The genomic analysis predicted proteins associated with dehydration and desiccation stress-response and the presence of genes that are directly related to osmotolerance and psychrotolerance in both novel yeasts described. Cells of these two newly-described yeasts were exposed to UV-C radiation and compared with N. onofrii, an extremophilic UV-C resistant cold-adapted Alpine yeast. Both novel species were UV resistant, emphasizing the need for collecting and characterizing extremotolerant microbes, including yeasts, to improve microbial reduction techniques used in NASA planetary protection programs.